Sunday Service at Unitarian Universalist Church of Fresno - Watkins, Howard::::::::: (1988)
Teacher is Paula Siegel; Margaret Olmos in green and red outfit and Robin Watkins in paisley dress, red-headed boys are Patrick Hatcher (blue) and Sean Hatcher (red)